Broadband photoelectric tunable quantum dot based resistive random access memory. Issue 6 (15th January 2020) - Chen, Zhiliang; Yu, Yu; Jin, Lufan; Li, Yifan; Li, Qingyan; Li, Tengteng; Li, Jie; Zhao, Hongliang; Zhang, Yating; Dai, Haitao; Yao, Jianquan
Abstract : Ultra-stable broadband photoelectric tunable PbS QD based RRAM device with flexibility and multilevel data storage ability was demonstrated. Abstract : Photoelectric resistive random access memory (RRAM) is a promising optoelectronic technology that is being developed to overcome the Von Neumann bottleneck and improve the computing and access performance of current computer systems. In this work, an ultra-stable broadband photoelectric tunable RRAM device based on PbS quantum dots (QDs) and poly(methyl methacrylate) (PMMA) hybrid materials was demonstrated. The device exhibits a long retention capability (>10 4 s), a high ON/OFF current ratio (10 4 ), fast response time (170 ns), cycle-to-cycle consistency, impressive environmental stability (>90 days) and flexibility. Multilevel data storage can be achieved through the appropriate setting of a series of compliance currents. In addition, the SET voltage of the device shows a broadband tunability from the ultraviolet (405 nm) to the near infrared (1177 nm). Furthermore, conductive atomic force microscopy (CAFM) measurements confirm that the formation and rupture of Ag conducting filaments are responsible for the resistive switching behavior. This study paves the way toward the development of next-generation high-density data storage technology and broadband photoelectric memory and computer technologies.